Principalsâ Leadership Style and Stress with Teacherâs Intention of Leaving the Teaching Profession - Din, Anuar; Alipin, Sabdin Hussin; Ambotang, Abdul Said (EDUCARE, 2014)
ABSTRACT: The principal plays an important entity in the schools success. In order to produce an excellent school, the principal must pay attention to good working conditions for teachers. Factors of the principalâs school management and leadership greatly affects aspects of teachers satisfaction and their comfort in handling their jobs as a teacher in the school. This study aims to investigate the leadership style and stress among teachers with the intention of leaving the teaching profession. A total of 165 respondents were involved in this study. This study is a survey using quantitative methods. The questionnaire used in this study. Data were analyzed by computer software Statistical Package for the Social Sciences (SPSS) version 20.0 using t-test, one way ANOVA, and Pearson correlation analysis; and the data obtained are described through descriptive statistics and inferential statistics. The results showed a significant relationship (r = .195, p < 0.05) between the style of leadership with the intention of leaving the teaching profession. The results also showed a significant correlation (r = .293, p < 0.01) between teacher stress with the intention to leave the teaching profession among teachers. In addition, the study also showed that the intention to leave the teaching profession based on demographic factors of gender, age, education level, job category, and length of service among teachers is simple. At the end of the discussion, the researchers expressed some implications of the study and further research recommendations.KEY WORDS: Leadership style, stress, intention of leaving the teaching profession, the role of teacher in Malaysia, and demographic factors.Â Â Â Â About the Authors: Dr. Anuar Din is a Senior Lecturer at the School of Education and Social Development UMS (Malaysia University of Sabah), 88400 Kota Kinabalu, Sabah, Malaysia; Sabdin Hussin Alipin is a Teacher at Sabah Education Department, Kota Kinabalu, Sabah, Malaysia and Graduate Master of Education (Education Management) from UMS; and Dr. Abdul Said Ambotang is a Senior Lecturer at the School of Education and Social Development UMS in Kota Kinabalu, Sabah, Malaysia. The authors can be contacted via e-mails address at: anudin@ums.edu.my, sabdyn_81@yahoo.com, and said@ums.edu.myHow to cite this article? Din, Anuar, Sabdin Hussin Alipin & Abdul Said Ambotang. (2014). âPrincipalsâ Leadership Style and Stress with Teacherâs Intention of Leaving the Teaching Professionâ in EDUCARE: International Journal for Educational Studies, Vol.7(1) August, pp.27-42. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (March 20, 2014); Revised (May 30, 2014); and Published (August 17, 2014).